Evaluation of the specificity of an intradermal test with recombinant tuberculosis allergen in Bacillus Calmette–Guérin-vaccinated healthy volunteers - Vasilyeva, Irina A.; Aksenova, Valentina A.; Kazakov, Alexey V.; Kiseleva, Yulia Y.; Maryandyshev, Andrey O.; Dolzhenko, Elena N.; Abramchenko, Anna V.; Klevno, Nadejda I.; Glebov, Konstantin A.; Panova, Anna E.; Petrova, Larisa Y.; Sheikis, Elena G.; et al. (Frontiers in medicine, 2023)
The tuberculin skin test has significant limitations for use in individuals vaccinated with BCG. The presence in the genome of of the RDI region, which is absent in the genome of Mycobacterium bovis BCG and most non-tuberculous mycobacteria, made it possible to develop new skin tests, which include a skin test with a recombinant tuberculosis allergen [RTA (Diaskintest®, JSC Generium, Russia)]. Diaskintest has shown high diagnostic performance in clinical trials and in conditions of high prevalence of tuberculosis infection. In 2021, the Russia was excluded from the WHO list of high TB burden countries, which makes relevant an assessment of the specificity of the RTA test under conditions of low epidemiologic risk for tuberculosis to confirm the high specificity of the test. To assess the specificity of Diaskintest in the regions of the Russian Federation with low epidemiologic risk for tuberculosis. A multicenter, open-label, prospective study was conducted, which included 150 healthy volunteers aged 18-30 years old, vaccinated with BCG, who were not at risk of tuberculosis, from regions with low epidemiologic risk (Oryol region, Ryazan region, and Arkhangelsk region). During the study, 4 visits were scheduled for each participant: [Visit 0 (screening), Visit 1, Visit 2 (in 72 h) and Visit 3 (in 28 days)]. All participants, who excluded active and latent tuberculosis infection, underwent a test with RTA. To assess the safety of RTA tests, all systemic and local adverse events that occurred during 28 days were recorded. The trial was filed in the NIH clinical trials database ClinicalTrials.gov (NCT05203068). In individuals with a negative T-SPOT.TB test, the specificity of the RTA test was 97% (95% CI: 92-99%) with a cut-off of >0 mm. The study findings confirm data 2009: 100.00 (95% CI: 94-100). When evaluating the safety of the RTA test during 28 days of follow-up, the participants did not report local and systemic adverse reactions that had a causal relationship with the RTA test. Diaskintest is highly specific and safe, therefore it is a valuable tool as a screening test for early detection of tuberculosis.